Hello English Application In Teaching Grammar for Junior High Schoolers in Palembang - Oktaverani, Dwi Andrea; Anggraini, Nike; Permana, Dio Resta (English Education: Jurnal Tadris Bahasa Inggris, 2024)
In the digital era, modern methods have transformed the learning process, offering various tools to enhance education. One such tool is the Hello English application, which serves as a learning medium for students. Grammar learning, often considered tedious when taught through traditional books, can become more engaging with this application. This study aimed to evaluate the effectiveness of the Hello English application in improving students’ understanding of grammar. The research employed a pre-experimental design with eighth-grade students from SMP T as the population. A sample of 25 students was selected from a total of 51. Data were analyzed using paired sample t-tests, with validity and reliability assessed through a Likert scale and Cronbach’s alpha. A normality test was conducted prior to analysis. The results revealed a significant improvement in grammar understanding. The paired sample t-test showed a t-value of 10.719 with a p-value of 0.01 (p < 0.05), indicating a meaningful difference between pre-test and post-test scores. These findings demonstrate that the Hello English application effectively enhanced students’ grasp of the simple present tense, proving its value as a grammar teaching tool for eighth-grade students at SMP T in the 2024/2025 academic year.